Dinâmica da serrapilheira e da microbiota em fitofisionomias de uma savana tropical - Rêgo, Vanessa Mendes (2020)
Tropical savannas are home to several highly heterogeneous phytophysiognomies resulting from the combination of environmental factors. The decomposition of litter in this environment is essential in the global carbon cycle and depends on the flow of nutrients from the decomposition of litter, as well as on the structure of the microbial community. Our hypothesis is that phytophysiognomies and seasonality affect the dynamics of litter and microbiota in the tropical savanna. The study was conducted in a tropical savannah region, located in the municipality of Santo Antônio de Leverger, MT, Brazil. The site is made up of different Cerrado vegetation types representative of a tropical savanna, namely: Cerradão, Cerrado Stricto Sensu, Miscelânia and Cambarazal. Collections took place throughout the study period in the dry and wet seasons. The data of production, accumulation, decomposition and chemical characteristics of the litter were analyzed, as well as the composition and structure of the community of microorganisms found in the litter, by dependent and independent methods of cultivation. The diversity of plant species and the dry season favor the production of litter, with decomposition of plant material occurring more quickly during the dry period. The litter presented more recalcitrant chemical characteristics during the rainy season. Seasonality is the main structuring factor of the litter microorganism communities in the tropical savanna, due to the humidity and availability of resources providing a fluctuation in the alpha diversity. However, during the dry period, bacterial and fungal interactions are more complex and more modularly structured in relation to the relationships observed in the networks obtained during the wet period. The microorganism community is classified mainly by niche division, showing that the abundance of specialist rates is dependent on the seasonality and structure of the vegetation. Making habitat fragmentation, as well as climate change, factors of concern for the future of the litter microorganism community in the tropical savanna.